Moving Metaphors: Shifting Institutional Responsibilities and Evidentiary Boundaries in the Commissioning of Pre-Exposure Prophylaxis for HIV. (August 2019) - Gee, Seran; Chum, Antony; Lim, Bryan
In this article, we investigate how speakers in the U.K.'s House of Commons cited the same legislative context and medical research to arrive at contradictory conclusions regarding the Government's responsibility to fund pre-exposure prophylaxis (PrEP) as an HIV intervention. Because the Government had expressed that it would not comment on institutional responsibilities directly, given the likelihood of a legal challenge in response to the National Health Service withdrawing PrEP from the drug commissioning process, the Government's support of this decision could not be explicitly detailed. Our discourse analytic approach reveals how members of parliament adopted positions in the debate by using distinct metaphorical frames and lexical choices to linguistically encode assumptions that imply contrary interpretations of mutually agreed upon facts. This suggests that the concrete discursive practices used to cite evidence in policy-making discussions, regardless of the quality of the evidence, may have material consequences for evidence-based policy.